ANALISIS PENDAPATAN DAN NILAI TAMBAH AGROINDUSTRI TAHU DAN TEMPE DI DESA BANDAR AGUNG KECAMATAN TERUSAN NUNYAI KABUPATEN LAMPUNG TENGAH - Desti Yuliatami; Muhammad Irfan Affandi; Eka Kasymir (Lampung University, 2021)
This study aims to analyze income and added value in tofu and tempe agroindustries in Bandar Agung Village Terusan Nunyai Subdistrict Lampung Tengah Regency. The data were collected in January - Febuary 2020 using a case study method. Agroindustry income is obtained from subtracting the total revenue by total costs and the calculation of added value uses Hayami value added method. The results of this study showed that profit of tofu production was IDR5,046,112.98/week and of tempe was IDR1,903,857.44/week with the R/C >1, meaning that the business was profitable and feasible. The calculation of added values of tofu and tempe agroindustries showed postive values with added value ratios of 56.75% of tofu agroindustry and 53.15% of the tempe agroindustry.Key words:income, added value, agroindustry, soybean